ERROR BEHAVIOR OF ATOMIC CLOCKS ABOARD GPS SATELLITES - Mansur, Gustavo Bento; Ferreira, Luiz Danilo Damasceno (Boletim de Ciências Geodésicas, 2019)
The signal transmission and position quality obtained by GNSS positioning directly depends on the time control. The atomic clocks aboard the satellites are responsible for this control. In this research, the satellites clock errors of GPS are studied, using data from the pseudorange, the satellite semi-major axis and the correction parameters of the satellites’ clock errors found in the RINEX navigation and observation files. From these data, the satellites’ clock errors are calculated using the IGS mathematical model for rubidium and cesium clocks, and then an adjustment technique is applied in order to estimate the new parameters of the clock corrections. For cesium atomic clocks, the periodic part of the mathematical model was adapted. The correction parameters adjusted were applied in the IGS and the adapted model; finally, the results were compared with the IGS data from the clk_30s file. The experiments carried out show an improvement of 50 cm in the cesium satellites’ clock errors. In addition, the research concludes that the satellites’ clock errors do not depend on the station where the data were collected and the equipment’s antenna.